2021
DOI: 10.1080/14685248.2021.1932944
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb-generated Reynolds-number-dependent wake turbulence

Abstract: We present an experimental and numerical study of the flow downstream of honeycomb flow straighteners for a range of Reynolds numbers, covering both laminar and turbulent flow inside the honeycomb cells. We carried out experiments with planar particle image velocimetry (PIV) in a wind tunnel and performed numerical simulations to perform an in-depth investigation of the three-dimensional flow field. The individual channel profiles downstream of the honeycomb gradually develop into one uniform velocity profile.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, if the average particle displacement is too large compared to the size of the interrogation windows, the number of spurious vectors and outliers drastically increases. Based on detailed studies of Thijs (2020) and Thijs et al (2021) on the number of filtered vectors as a function of window size and average particle displacement, the present study uses an initial pass with interrogation windows with a size of 64 × 64 pixels and an overlap of 50%. Afterwards, four additional passes are performed with a window size of 32 × 32 pixels and an overlap of 50%.…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if the average particle displacement is too large compared to the size of the interrogation windows, the number of spurious vectors and outliers drastically increases. Based on detailed studies of Thijs (2020) and Thijs et al (2021) on the number of filtered vectors as a function of window size and average particle displacement, the present study uses an initial pass with interrogation windows with a size of 64 × 64 pixels and an overlap of 50%. Afterwards, four additional passes are performed with a window size of 32 × 32 pixels and an overlap of 50%.…”
Section: Particle Image Velocimetrymentioning
confidence: 99%
“…Honeycombs are particularly effective for reducing large-scale swirling fluid motion (Farell and Youssef, 1996) and prevent the uncontrollable growth of turbulence by inhibiting the lateral components of the fluctuating velocity (Loehrke and Nagib, 1976). However, despite reducing the turbulence level of the feed stream, honeycombs may produce new vigorous turbulence near their discharge due to the formation of large-scale instabilities and the break-up of the individual velocity profiles stemming from the honeycomb cells (Thijs et al, 2021). In spite of the extensive research on turbulence suppression by honeycombs, studies on methods to reduce the turbulence generated by honeycombs are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With the innovative planar magnet [21] and synthesis method of magnetic fluid [22,23], Peter Rem et al successfully industrialized the MDS for plastic sorting with a certain design of separation channel which facilities are being used by Umincorp in the Netherlands [24,25]. In the separation channel [26], a magnetic fluid is continuously flowing horizontally and transporting fed particles through a laminator, a separation zone, and a collection zone in sequence. The laminator creates a laminar fluid flow for the separation zone.…”
Section: Introductionmentioning
confidence: 99%
“…The throughput of this system depends on the fluid flow velocity because the particles are conveyed by the fluid, but increasing the fluid velocity could cause more turbulence that may affect the separation accuracy in the separation zone. Corresponding studies were carried out to examine the turbulence effect [26][27][28] and suggested to carefully design the structure and control the fluid velocity. In addition, if a particle entering the splitter zone has a dimension larger than the distance between two splitter walls (e.g.…”
Section: Introductionmentioning
confidence: 99%